Quantum dots in organic electronics: from solar cells to sensors - Torres, F.G.; Troncoso, O.P.; Tapia, J. (Elsevier, 2025)
Quantum dots (QDs) feature optical and electronic properties that are determined by their size. This allows for tailored functionalities such as specific emission wavelengths, high photostability, and efficient charge transport, making QDs suitable for integration into electronic devices. Organic electronics represent an environmentally friendly alternative to traditional silicon-based technologies. However, organic electronic devices typically suffer from lower performance. This review examines the role of QDs in enhancing the performance of organic electronic devices, with a focus on solar cells, light-emitting diodes (LEDs), thin-film transistors (TFTs), and sensors. In solar cells, QDs enhance power conversion efficiency through optimized bandgap engineering. In LEDs, QDs contribute to superior color purity, and brightness. In TFTs, QDs help improve field-effect mobility and device stability. In sensors, QDs provide enhanced sensitivity and selectivity. This review aims to provide a comprehensive overview of how QDs are being leveraged to address the limitations of conventional organic electronic technologies.
Keywords: Quantum dots (QDs); Quantum confinement effect; Excitons; https://purl.org/pe-repo/ocde/ford#1.03.02